Qualitative Study: The Relationship Between The Head of Unit's Leadership Model and Retention Program With The Turnover Intention of New Nurses In Private Hospital X South Jakarta - Meilina, Herlina; Buka, Sisilia Prima Yanuaria; Hotmaidah, Sondang; Sihombing, Jenny; Sidabalok, Masniati (Indonesian Scientific Publication, 2025)
The transition period for new nurses when entering the workforce and joining a nursing unit is an important period. The role of the head of the room as a first-line manager is also very important in planning, organizing, leading, directing, supervising and evaluating the process of implementing nursing care by new nurses. To explore the relationship between the unit head's leadership model and retention program with the turnover intention of new nurses in the Hospital. This study uses a qualitative research method with a descriptive phenomenological approach. The sampling technique used is systematic purposive sampling (Systematic Purposive Sampling). The population of new nurses for the period January-March 2021 was 100 people. The research sample is the population of each serial number 1, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 or a total of 11 samples. This sample will undergo in-depth interviews and FGDs, for 6 weeks on June 14 - July 26, 2021. We use qualitative content analysis and cross-case analysis techniques with the nvivo 12 plus software program. The result of this study Identified and explored the experiences of new nurses towards the leadership model of the head of the room, retention programs and turnover intentions at Private Hospital X, South Jakarta. The results of the study found: transformational leadership models, career ladder programs, orientation programs and professional development programs have an influence on preventing turnover intentions of new nurses.